Determinan Indeks Pembangunan Manusia (IPM) di Indonesia Tahun 1990-2021 - Mailadani, Diah Ayu; Syafri, Syafri; Rosintan S, Lydia (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2024)
One of the factors that determines the welfare of a country's people is the Human Development Index (HDI). The aim of this research is to analyze the influence of unemployment, inflation, foreign direct investment and net exports on the Human Development Index in Indonesia. The analysis method used is the Autoregressive Distributed Lag (ARDL) model. The data used is annual data for the 1990-2021 period obtained from the United Nations Development Program and the World Bank. The research results show that unemployment, inflation, foreign direct investment and net exports have a significant effect on HDI in the short term. In the long term, only the unemployment rate has a significant effect on HDI. Net exports have a positive influence on HDI while inflation has a negative impact on HDI in the short term. Current foreign direct investment and current unemployment rate have a positive effect on HDI in the short term. However, the influence of lag one to lag 3 of foreign direct investment  and the unemployment rate on HDI is negative.